2021
DOI: 10.12688/wellcomeopenres.16978.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood meal analysis of tsetse flies (Glossina pallidipes: Glossinidae) reveals higher host fidelity on wild compared with domestic hosts

Abstract: Background: Changes in climate and land use can alter risk of transmission of parasites between domestic hosts and wildlife, particularly when mediated by vectors that can travel between populations. Here we focused on tsetse flies (genus Glossina), the cyclical vectors for both Human African Trypanosomiasis (HAT) and Animal African Trypanosomiasis (AAT). The aims of this study were to investigate three issues related to G. palldipes from Kenya: 1) the diversity of vertebrate hosts that flies fed on; 2) whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…It was therefore not surprising that tsetse flies in Shimba Hills were found to have fed frequently on cattle. A contrary finding by Channumsin et al [12] in Shimba Hills of absence of cattle bloodmeals in tsetse flies may be the result of sampling bias occasioned by the short sampling time (of less than five weeks) reported in that study.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…It was therefore not surprising that tsetse flies in Shimba Hills were found to have fed frequently on cattle. A contrary finding by Channumsin et al [12] in Shimba Hills of absence of cattle bloodmeals in tsetse flies may be the result of sampling bias occasioned by the short sampling time (of less than five weeks) reported in that study.…”
Section: Discussioncontrasting
confidence: 83%
“…Baboons, like goats and impala, display defensive behaviors against tsetse flies, hence it was not surprising that seven of the twelve sets of multiple hosts involved baboons. Disruption of tsetse-feeding before repletion on a host causes the vectors to switch to other hosts to continue feeding, thus allowing trypanosome-dissemination among and between wildlife and livestock [3,12]. In Shimba Hills, over half the cases of multiple-host feeding involved wildlife and livestock, prominently baboons and sheep, and warthogs and cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, field studies that investigate tsetse-trypanosome interactions are limited. Moreover, there are yet fewer studies that explore tsetse-host interactions, particularly in wildlife areas such as Shimba Hills (Kenya) where Channumsin et al ( 3 ) observed human and wildlife but not cattle bloodmeals in tsetse flies.…”
Section: Introductionmentioning
confidence: 99%